Corruption in Reconstruction and Development Programme (RDP) houses with special reference to Maphata Village, Ward 26 in Mopani District of Limpopo Province, South Africa - Ngobeni, Ellah Nkhensani (My University, 2007)
The Maphata Village in Ward 26, under the jurisdiction of Greater Giyani Local Municipality in Mopani District- Limpopo Province, was allocated 70 seventy (70) Reconstruction and Development Programme houses during the 2001/2002 and 2005/2006 Financial Years respectively. During the process, there were allegations from members of the community that there were corrupt practices with regard to the allocation of the Reconstruction and Development Programme houses as more that fifty (51) beneficiaries were relatives of the Ward Councillor. Since there is lack of research that looked at corruption on the allocation of Reconstruction and Development Programme houses, the present study aimed to assess the level of beneficiaries’ knowledge on corrupt practices (level of understanding) so that they can be encouraged to blow a whistle on corruption within their environment; to assess the beneficiaries’ level of understanding regarding corruption and their awareness of corrupt practices, evaluate Reconstruction and Development Programme houses Allocation Strategy; probe the nature and extent of corruption on Reconstruction and Development Programme houses; and provide possible mechanisms against the problem of corruption. The study was critical and important as provision of houses is one of the basic needs to the poor community and, as such, the Limpopo Province cannot afford to neglect this responsibility. The Parliament of the Republic of South Africa recognises amongst others, that: • housing as an adequate shelter, fulfils a basic human need; • housing is both a product and process; • housing is a key sector of the national economy; and • housing is vital to the socio-economic well-being of the nation. (iii) The findings of the study and the recommendations if implemented will improve the status of the corruption of the allocation of RDP houses to the vulnerable groups. (iv)
Thesis (M.A. (Public Administration)) --University of Limpopo, 2007
Keywords: Reconstruction and Development Programme; Housing; Public housing -- Corrupt practice -- South Africa; Community development, Rural -- South Africa